Unveiling barriers to reproductive health awareness among rural adolescents: a systematic review - Wahyuningsih, Sri; Widati, Sri; Praveena, Sarva Mangala; Azkiya, Mohammad Wavy (Frontiers in Reproductive Health, 2024)
IntroductionSexual and reproductive health (SRH) among adolescents is a critical aspect of global health. Rural adolescents often encounter significant barriers to reproductive health awareness, elevating their risks for unintended pregnancies, sexually transmitted infections (STIs), and other reproductive health issues. This systematic review seeks to identify and analyze the barriers hindering reproductive health awareness among rural adolescents.MethodsThis review followed PRISMA guidelines. Literature searches were conducted in PubMed, ScienceDirect, Google Scholar, and Taylor & Francis, focusing on studies published from 2019 to 2024. Keywords included “Adolescent,” “Rural,” “Reproductive Health,” “Awareness,” and “Barriers.” Studies were screened based on eligibility criteria, and data were extracted and analyzed to identify key barriers at the individual, interpersonal, social/community, and health services levels.ResultsOut of 669 records, 20 studies met the inclusion criteria. Identified barriers at the individual level included lack of knowledge, myths, misconceptions, and feelings of shame and fear. Interpersonal barriers were related to poor communication between parents and adolescents and misinformation from peers. Social and community barriers encompassed rigid social norms, stigma, and discrimination. Health services barriers included limited access and negative experiences with reproductive health services.DiscussionRural adolescents face complex barriers to reproductive health awareness driven by factors at the individual, interpersonal, social, and health services levels. Comprehensive interventions, such as educational campaigns, training for healthcare providers, and improved access via mobile or online platforms, are essential to enhance reproductive health awareness and outcomes.Systematic Review Registrationhttps://www.crd.york.ac.uk/, PROSPERO (CRD42024554439).